The Correlation Between the Prevalence of Anemia in Pregnant Women and Their Awareness and Use of Iron Supplementation in the Work Area of the Curup Health Center - Emilia Silvana Sitompul; Wita Solama (CV. Get Press Indonesia, 2025)
In Indonesia, anemia during pregnancy remains a major public health issue due to its risks for both mother and baby. This study aims to analyze the relationship between anemia in third-trimester pregnant women and their knowledge and behavior regarding iron (Fe) tablet consumption. Conducted in the Curup Health Center area, this cross-sectional study used a descriptive analytical design with purposive sampling to select 35 pregnant women as respondents.Data were collected through hemoglobin testing using the Easy Touch GCHb device and questionnaires assessing knowledge and behavior. The results showed that 71.4% of respondents did not experience anemia, 60% demonstrated positive behavior in consuming Fe tablets, and 51.4% had sufficient knowledge about anemia and iron supplementation.The chi-square test indicated no significant relationship between knowledge and the incidence of anemia (p = 0.240). However, a significant relationship was found between behavior in consuming Fe tablets and the occurrence of anemia (p = 0.002).These findings suggest that while knowledge alone may not prevent anemia, consistent and proper behavior in taking Fe tablets has a stronger influence. Therefore, enhancing behavioral-based education and monitoring could help improve adherence to Fe tablet intake and reduce anemia prevalence among pregnant women.